Analysis of Marketing Mix Strategies in Increasing Room Revenue on Grand Inna Kuta Bali - Bibit Bintang Bithara; I Ketut Astawa; Nyoman Rajin Aryana; Made Ruki (Journal of Applied Sciences in Travel and Hospitality, 2020)
This study discusses strategies in increasing revenue at Grand Inna Kuta with marketing mix. The purpose of this study was to analyze the strengths and weaknesses of the marketing strategies adopted by Grand Inna Kuta. The number of respondents used was 16 respondents, with a purposive sampling data collection technique. The method of primary data collection with a focus group discussion (FGD) method by involving several people from sales and marketing at Grand Inna Kuta. The analysis technique used is the SWOT analysis technique (Strengths, Weaknesses, Opportunities, and Threats). The results showed that 7 internal indicators that become strengths, and 4 internal indicators that become weaknesses. On the other hand, there are 3 external indicators that are opportunities, and there are 3 external indicators that threats. In the SWOT matrix analysis technique, there are 2 strategies were obtained to maximize strength and opportunity there are intensify the promotion to government market, and intensify the room packages based on the current season. Two strategies to maximize strengths to minimize threats which are adjust the room price to make it lower, and focus on the current target market. Two strategies to maximize opportunities by minimizing weaknesses which are rejuvenate or repair the room ambiance, and technology for paying method. Four strategies to minimize challenges and weaknesses contains of increase evaluating of the staff to work by giving rewards, train more about the skill quality for the staff, create support package, and make a promotion on airline.